Improving policy coherence in food, land, and water systems to advance sustainable development in India: a case study of Odisha - Council on Energy, Environment and Water (CEEW); International Water Management Institute (International Water Management Institute (IWMI). CGIAR Initiative on National Policies and Strategies, 2024)
Food, land, and water (FLW) systems are closely interlinked; actions in one system often impact the others. Enhancing the sustainability of these interconnected systems is crucial for advancing food security, sustainable livelihoods, rural development, environmental health, and climate resilience. Recognising these interlinkages, India is making significant policy efforts to achieve environmental, economic, and social well-being (PIB 2024a). However, the complexity and evolving nature of these interlinkages necessitate coherent policy efforts (CEEW and IWMI 2023).